2005
DOI: 10.1007/bf02724027
|View full text |Cite
|
Sign up to set email alerts
|

Abstract

Abstract: Abstract. Yolk sac tumors are common in children. By virtue of being chemosensitive, they are amenable to cure by chemotherapy alone and radical surgery is often not required. Yolk sac tumors occurring in the vagina are rare and thus may not be recognized early or may be inadvertently subjected to radical surgery. The authors report a case that presented to them after radical surgery with elevated Alpha-fetoprotein level is reported. The management of this case and review of the relevant literature are discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although immunostaining for AFP has traditionally been considered to support a diagnosis of EST, it is relatively nonspecific. 6 In most of the earlier case reports also, the diagnosis of EST was confirmed on the basis of histological features, presence of diastase resistant PAS stain positive hyaline globules and raised serum AFP 3 , 7 . ESTs are CK7, Leu-M1, and EMA negative, in contrast to clear cell carcinomas 6 , 8 …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although immunostaining for AFP has traditionally been considered to support a diagnosis of EST, it is relatively nonspecific. 6 In most of the earlier case reports also, the diagnosis of EST was confirmed on the basis of histological features, presence of diastase resistant PAS stain positive hyaline globules and raised serum AFP 3 , 7 . ESTs are CK7, Leu-M1, and EMA negative, in contrast to clear cell carcinomas 6 , 8 …”
Section: Discussionmentioning
confidence: 90%
“…Aberrant migration of germ cells during early embryonic life has been implicated as a possibility of origin. Clinical presentation is with a polypoid vaginal mass, bloody discharge or sometimes even urinary retention if the bladder is compressed 3 . We report two cases of endodermal sinus tumor in infants, located in the vagina, which is a very rare site and serum alpha-fetoprotein level is elevated in both the cases.…”
Section: Introductionmentioning
confidence: 91%
“…But isolated injury to the face due to low voltage cells exploding is extremely rare in literature. [12]…”
Section: Introductionmentioning
confidence: 99%
“…Dusmet et al reported a vestigial tail in an infant with most of the major and minor defects of the VATER syndrome (see Abbreviations) including imperforate anus [3]. A true tail has also been reported in association with sirenomelia including the feature of anal atresia [4,5]. Kahler et al reported a case of pygomelus (a pseudotail variant) in association with lipomyelomeningocele and an incomplete expression of Currarino's triad including anal atresia with recto-vaginal fistula [6].…”
Section: Introductionmentioning
confidence: 99%